Bioconversion of Olive Pomace: A Solid-State Fermentation Strategy with Aspergillus sp. for Detoxification and Enzyme Production - Rodríguez, Laura A. (2025)
This study aimed to evaluate solid-state fermentation (SSF) as a sustainable approach forthe simultaneous detoxification of olive pomace (OP) and the production of industriallyrelevant enzymes. OP, a semisolid byproduct of olive oil extraction, is rich in lignocelluloseand phenolic compounds, which limit its direct reuse due to phytotoxicity. A native strainof Aspergillus sp., isolated from OP, was employed as the biological agent, while grapepomace (GP) was added as a co-substrate to enhance substrate structure. Fermentationswere conducted at two scales, Petri dishes (20 g) and a fixed-bed bioreactor (FBR, 2 kg),under controlled conditions (25 ◦C, 7 days). Key parameters monitored included dry andwet weight loss, pH, color, phenolic content, and enzymatic activity. Significant reductionsin color and polyphenol content were achieved, reaching 68% in Petri dishes and 88.1%in the FBR, respectively. In the FBR, simultaneous monitoring of dry and wet weight lossenabled the estimation of fungal biotransformation, revealing a hysteresis phenomenonnot previously reported in SSF studies. Enzymes such as xylanase, endopolygalacturonase,cellulase, and tannase exhibited peak activities between 150 and 180 h, with maximumvalues of 424.6 U·g−1, 153.6 U·g−1, 67.43 U·g−1, and 6.72 U·g−1, respectively. The experi-mental data for weight loss, enzyme production, and phenolic reduction were accuratelydescribed by logistic and first-order models. These findings demonstrate the high metabolicefficiency of the fungal isolate under SSF conditions and support the feasibility of scalingup this process. The proposed strategy offers a low-cost and sustainable solution for OPvalorization, aligning with circular economy principles by transforming agro-industrialresidues into valuable bioproducts.